2022
DOI: 10.5852/ejt.2022.833.1887
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic implications of describing a new species of Loimia (Annelida, Terebellidae) with two size-dependent morphotypes

Abstract: We describe Loimia davidi sp. nov. (Annelida, Terebellidae) from São Miguel Island (Azores). It resembles Loimia gigantea (Montagu, 1819) (English Channel) in having very large adults, the ventral shield shape and the types of capillary notochaetae (three), while differing in shape and colour of the lateral lappets, branchiae length, the arrangement of segments, ventral shields, uncini and pygidial papillae. Large (> 30 cm long) and small (≈ 5 cm long) specimens of L. davidi sp. nov. show typically interspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…At present, the polychaetes comprise nearly 11,500 accepted nominal species ( Pamungkas et al, 2019 ; Read, 2019 ), and are one of the most abundant and diverse groups of invertebrates in soft marine bottoms worldwide ( Hutchings, 1998 ; Brooks et al, 2006 ; Pamungkas et al, 2019 ; Pamungkas, Glasby & Costello, 2021 ). However, according to Read (2019) , it could be that as much as 60–65% of the species remain undescribed, thus limiting our knowledge of their role on the ecology and evolutionary processes operating in benthic ecosystems ( Martin et al, 2022 ). This is the case of the Longosomatidae ( Hartman, 1944 ), a marine benthic family poorly known worldwide, and particularly in the Gulf of California, where only one valid species, H. catalinensis ( Hartman, 1944 ) collected at 1,550–1,590 m depth by Mendez (2006) and Mendez (2007) and an unnamed species ( Heterospio sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the polychaetes comprise nearly 11,500 accepted nominal species ( Pamungkas et al, 2019 ; Read, 2019 ), and are one of the most abundant and diverse groups of invertebrates in soft marine bottoms worldwide ( Hutchings, 1998 ; Brooks et al, 2006 ; Pamungkas et al, 2019 ; Pamungkas, Glasby & Costello, 2021 ). However, according to Read (2019) , it could be that as much as 60–65% of the species remain undescribed, thus limiting our knowledge of their role on the ecology and evolutionary processes operating in benthic ecosystems ( Martin et al, 2022 ). This is the case of the Longosomatidae ( Hartman, 1944 ), a marine benthic family poorly known worldwide, and particularly in the Gulf of California, where only one valid species, H. catalinensis ( Hartman, 1944 ) collected at 1,550–1,590 m depth by Mendez (2006) and Mendez (2007) and an unnamed species ( Heterospio sp.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we observed that the addition of quantitative features provided important additional information to support the discrimination between polychaete taxa, mainly when the examined specimens exhibit morphological variability. For example, we used multivariate morphometric analysis to separate closely related species and erect the new orbinid Leitoscoloplos multipapillatus ( Hernández-Alcántara & Solís-Weiss, 2014 ); also, Hernández-Alcántara, Mercado-Santiago & Solís-Weiss (2017) analyzed the morphometric variability of the onuphid Paradiopatra multibranchiata to determine the main characters supporting its description as a new species; Martin et al (2022) described the new terebellid Loimia davidi , examining the taxonomic implications of size-dependent morphological characters and its differences with close species using hypervolume analysis, and summarizing the morphological information of all known species of Loimia ; Molina-Acevedo, Fernández-Rodríguez & Idris (2022) carried out a morphometric approach to separate the eunicids Paucibranchia belli , P. disjuncta and P. carrerai , evaluating the importance of 23 morphological features and their correlation with the individuals’ size to discriminate species within the genus. Additionally, the relationships between the environmental variables and the distribution of the new species along the Gulf of California shelf were also examined to improve the knowledge about the poorly known ecology of the longosomatids.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Loimia comprises 31 valid species (Read and Fauchald, 2023), mostly distributed in the southern hemisphere, and living in coastal and intertidal habitats (Hutchings et al, 2021). Although new species have recently been described from Australia (Nogueira et al, 2015), Brazil (Carrerette and Nogueira, 2015), China (Wang et al, 2020), and Europe (Lavesque et al, 2017;Martin et al, 2022), the systematics of this genus is still quite challenging. Indeed, many species have been described a long time ago with original descriptions being inadequate and type specimens often lost or not designated (Lavesque et al, 2021).…”
Section: Introductionmentioning
confidence: 99%